2019
DOI: 10.3390/ijms20030738
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of Biologically Significant Genes and Associated Molecular Pathways in the Oral Epithelium of Electronic Cigarette Users

Abstract: We have investigated the regulation of genes and associated molecular pathways, genome-wide, in oral cells of electronic cigarette (e-cigs) users and cigarette smokers as compared to non-smokers. Interrogation of the oral transcriptome by RNA-sequencing (RNA-seq) analysis showed significant number of aberrantly expressed transcripts in both e-cig users (vapers) and smokers relative to non-smokers; however, smokers had ~50% more differentially expressed transcripts than vapers (1726 versus 1152). Whereas the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(101 citation statements)
references
References 46 publications
5
70
0
4
Order By: Relevance
“…The "Wnt/Ca + pathway" in e-cig users and the "integrin signaling pathway" in smokers were the most affected pathways in the canonical pathways and networks modulated. For both e-cig users and smokers, the "Rho family GTPases signaling pathway" was the top disrupted pathway amongst the overlapping functional pathways, although the number of affected targets was three times higher in smokers than e-cig users [87].…”
Section: Studies On Other Effects Of Ends In the Oral Cavitymentioning
confidence: 99%
“…The "Wnt/Ca + pathway" in e-cig users and the "integrin signaling pathway" in smokers were the most affected pathways in the canonical pathways and networks modulated. For both e-cig users and smokers, the "Rho family GTPases signaling pathway" was the top disrupted pathway amongst the overlapping functional pathways, although the number of affected targets was three times higher in smokers than e-cig users [87].…”
Section: Studies On Other Effects Of Ends In the Oral Cavitymentioning
confidence: 99%
“…More recently, DNA hydroxymethylation has also emerged as an important mechanism of gene deregulation in human carcinogenesis [11,12]. Building on our recent findings [6], we have now investigated the association between vaping and these key epigenetic effects in a well-defined population of exclusive e-cig users, smokers only, and control non-vapers non-smokers, matched for age, gender, and approximately race (n = 15, each group). We have quantified DNA methylation levels in Long Interspersed Nucleotide Element 1 (LINE-1) repeats, as an indicator of global 5-methylcytosine (5-mC) content of the DNA [10,13], and measured global levels of 5-hydroxymethycytosine (5-hmC), which is the oxidation product of 5-mC [11,12], in leucocytes DNA from the study population, using enzyme-linked immunosorbent assays (ELISA).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have demonstrated that vapers, similarly to smokers, exhibit differential expression of genes in the oral epithelium, a major target organ for smoking-associated cancer [6]. The cancer-causing effects of many carcinogens present in both e-cig vapour and cigarette smoke are ascribed to their ability to induce genetic and/or epigenetic alterations [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, evidence-based regulations and scientifically driven recommendations on vaping will not only be more effective, sensible, and enforceable, but they will also minimize/eliminate the risk of unintended outcomes, such as inadvertently turning e-cigs into a "prohibitos autem fructum" (translation: forbidden fruit). While research data are accumulating on the adverse biological effects of e-cig use [18][19][20], evidence is also emerging on the efficacy of vaping combined with behavioral therapy in helping smokers quit [21] (although initial studies have produced mixed results [22]). The existing data clearly demonstrate that vaping is not risk free.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%